Prevalence of Trichomonas vaginalis Based on Clinical Manifestation and Polymerase Chain Reaction among Reproductive Women - Huriyah Hafizhotul 'Ummah; Gita Widya Pradini; Reiva Farah Dwiyana; Muhammad Ersyad Hamda (Faculty of Medicine Universitas Padjadjaran, 2019)
Objective: To measure the prevalence of Trichomonas vaginalis (T. vaginalis) based on clinical manifestations and polymerase chain reaction (PCR) among reproductive women.Methods: Subjects of the study were the vaginal swab obtained from reproductive women who attended the gynecology examination at Kandanghaur and Sindang primary health care of Indramayu District, West Java in 2016. This study was a descriptive study with cross-sectional method. Sampling was performed with total sampling method and 76 of vaginal swabs were included in this study. The prevalence of T. vaginalis was measured using PCR. The vaginal specimens were collected and then processed for PCR analysis using TVK3/TVK7.Results: Prevalence of T. vaginalis among reproductive women in Indramayu District, West Java that analyzed using PCR was 0%. This result could be affected by the study setting in community, presence or absence of symptoms, and population studied.Conclusion: There were no positive results of T. vaginalis, suggested by the samples that obtained from community-based of a low-risked population.Keywords: Trichomonas vaginalis, polymerase chain reaction, prevalence, reproductive women